Training programs used by French professional coaches to increase ball throwing velocity of elite handball players - Laffaye, G.; Debanne, T. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The goal of this study is to understand through a survey how professional French handball players build their training program (TP). Results show that: 1) the time allotted to ball throwing velocity is a large part of the TP, 2) they based their TP on an accurate analysis of the ball throwing technique and 3) without academic background, coaches used beliefs rather than scientific knowledge to build their TP.